Fabrication of Zirconia-Reinforced Lithium Silicate Ceramic Restorations Using a Complete Digital Workflow - Sven Rinke; Matthias Rödiger; Dirk Ziebolz; Anne-Kathrin Schmidt (Case Reports in Dentistry)
This case report describes the fabrication of monolithic all-ceramic restorations using zirconia-reinforced lithium silicate (ZLS) ceramics. The use of powder-free intraoral scanner, generative fabrication technology of the working model, and CAD/CAM of the restorations in the dental laboratory allows a completely digitized workflow. The newly introduced ZLS ceramics offer a unique combination of fracture strength (>420 MPa), excellent optical properties, and optimum polishing characteristics, thus making them an interesting material option for monolithic restorations in the digital workflow.